Long-term Outcome of Synthetic Mesh Use in Iranian Women with Genital Prolapse - Bastani, Parvin; Hajebrahimi, Sakineh; Mallah, Fatima; Chaichi, Parastoo; Sadeghi Ghiasi, Fatemeh (Urology Journal, 2020)
Purpose: To evaluate the long-term outcome of synthetic mesh use in the treatment of women with Pelvic organ prolapse (POP). Materials and Methods: We evaluated the outcome of synthetic mesh implantation by vaginal surgery method in 153 women (mean age of 53.66±9.31 years) with POP grade >2 in the anterior compartment. Demographic findings, baseline symptoms as well as subjective and objective outcome were recorded during the follow-up period of 36.89±11.33 months. Results: POP relapse occurred in 3.3% indicative of 96.7% anatomical success rate. Patients’ common baseline findings were frequency (72.5%), stress and urge incontinence (59.5% and 47.7%). Subjective outcome were vaginal pain (13.7%), dyspareunia (9.2%) and tension feeling (8.5%), while objective outcomes were mesh exposure (3.9%), urge incontinence (11.1%) and vaginal infection (1.3%). Stress incontinence was completely treated following surgery. There was significant improvement in dyspareunia, vaginal pain, urge and stress incontinence (all p < 0.001) and fecal incontinence (p = 0.02). After surgery, 88.42% were satisfied of the surgery outcome. Conclusion: POP surgery with synthetic mesh has acceptable results, considerable improvement in symptoms and high rate of satisfaction during follow-up; however, side effects are not uncommon but tolerable.